Intra-operative local plus systemic tranexamic acid significantly decreases post-operative bleeding and the need for allogeneic blood transfusion in total knee arthroplasty - Lidia De Falco; Elisa Troiano; Martina Cesari; Pietro Aiuto; Giacomo Peri; Nicolò Nuvoli; Mattia Fortina; Nicola Mondanelli; Stefano Giannotti (Medicinski glasnik, 2020)
Aim: To evaluate the efficacy of systemic plus local tranexamic acid (TXA) in reducing post-operative bleeding, haemoglobin loss and the need for allogeneic blood transfusion (ABT) in total knee arthroplasty (TKA). Methods: All patients undergoing TKA between January 2017 and September 2019 were retrospectively evaluated. Exclusion criteria were cardiovascular comorbidities, diabetes and the assumption of any anticoagulant/antiaggregant therapy in the pre-operative period. All patients received the same prosthesis with the same surgical technique and were operated on by the same surgeon. Twenty patients were found (group A) that received intra-operative TXA (20 mg/kg intravenous 10 minutes before deflating tourniquet and 1g intra-articular after capsular suture). A control group of 26 patients not receiving TXA was matched for demographics (group B). Results: Two (10%) patients in group A and 16 (61.5%) in group B needed ABT in the post-operative period (p=0.0004). Each patient in group A received 2 red blood cells (RBCs) units, while in group B 2 patients received one RBCs unit and one patient 4 RBCs units, for a total of 4 and 32 RBCs units in group A and B, respectively (p=0.0006). The minimum haemoglobin level was observed at 48 hours post-operatively in both groups: mean decrease was 3.54 and 4.64 g/dL in group A and B, respectively (p=0.0126). Conclusion: The association of systemic and local TXA administration seems to significantly reduce post-operative bleeding and the need for RBCs transfusions after TKA in patients not assuming any anticoagulant / antiaggregant therapy and without cardiovascular and diabetic morbidities.
Keywords: bleeding; haemoglobin; orthopaedic surgery; postoperative anaemia; red blood cells